Expanding the Role of Pharmacists and Pharmacy Students in the Promotion of Organ Donation Awareness. (June 2014) - Descourouez, Jillian L.; Richards, Katelyn R.; Sam, Teena; Crowther, Barrett
The gap between supply and demand for available organs has resulted in numerous deaths of patients on the transplant waiting list each year. Given the substantial public health impact of the organ shortage crisis, efforts have been focused on the use of educational interventions aimed both at the public and health care professionals to spread awareness of the disparity in organ supply and demand and ultimately improve organ donation rates. Transplant pharmacists are fundamental members of transplant multidisciplinary teams and are expected to promote organ and tissue awareness in an effort to decrease the morbidity and mortality of patients on the transplant waiting list. The role of pharmacists and pharmacy students in the promotion of organ donation awareness is expanding.